Synthesis of Lignin-based Phenol Terminated Hyperbranched Polymer - Lionel Longe; Gil Garnier; Kei Saito (Molecules, 2019)
In this work, we proved the efficient synthesis of a bio-based hyper-branched polyphenol from a modified lignin degradation fragment. Protocatechuic acid was readily obtained from vanillin, a lignin degradation product, via alkaline conditions, and further polymerised to yield high molecular weight hyperbranched phenol terminated polyesters. Vanillic acid was also subjected to similar polymerisation conditions in order to compare polymerisation kinetics and differences between linear and hyperbranched polymers. Overall, protocatechuic acid was faster to polymerise and more thermostable with a degradation temperature well above linear vanillic acid polyester. Both polymers exhibited important radical scavenging activity (RSA) compared to commercial antioxidant and present tremendous potential for antioxidant applications.